Effects of biochar application and nutrient fluctuation on the growth, and cadmium and nutrient uptake of Trifolium repens with different planting densities in Cd-contaminated soils - Zheng, Wei-Long; Wang, Yan-Fei; Mo, Jingya; Zeng, Pu; Chen, Jiayi; Sun, Chenliang (Frontiers in Plant Science, 2023)
Biochar has been used to remediate contaminated-soil with heavy metals, however, less is known on how biochar interacts with planting density and nutrient fluctuation to affect the remediation. A pot experiment was conducted in the greenhouse to investigate the effects of biochar application (without vs. with 1% biochar, g/g substrate), nutrient fluctuation (constant vs. pulsed) and planting density (1-, 3-and 6-individuals per pot) on the growth, and cadmium (Cd) and nutrient uptake of Trifolium repens population.Our results found that the growth of T. repens population increased significantly with increasing planting density, and the increment decreased with increasing planting density. Both the Cd and nutrient uptake were higher at higher planting density (e.g., 3and 6-individuals) than at lower planting density (e.g., 1-individual). Biochar application increased the biomass and shoot Cd uptake, but decreased the ratio of root to shoot and root Cd uptake of T. repens population, the effects of which were significantly influenced by planting density. Although nutrient fluctuation had no effect on the growth of T. repens population, but its interaction with planting density had significant effects on Cd uptake in tissues. Overall, the effects of biochar application and nutrient fluctuation on the growth and Cd uptake were both influenced by planting density in the present study. Our findings highlight that biochar application and constant nutrient supply at an appropriate planting density, such as planting density of 3individuals per pot in the present study, could promote the growth, and Cd and nutrient uptake of T. repens population.